Overview of the Total Bacteria and Number of Streptococcus mutans in the Saliva of Children with High Caries Activity - Natasya Putri Hardini Yanis; Tri Putriany Agustin (Indonesian Dental Association, 2020)
Introduction: Microorganisms play a crucial role in the early stage of caries. Streptococcus mutans produces lactic acid, which enhances the risk of caries. Polymerase chain reaction (PCR) is a molecular biology technique used in the amplification and replication of DNA. PCR exhibits high specificity and a rapid detection time, as well as differentiation between microorganisms. Based on a previous study, there is a significant correlation between S. mutans in saliva and the prevalence of caries. Objectives: To provide an overview of the total bacteria and number of S. mutans in the saliva of children aged between 5 and 10 years at the Department of Pediatric, Faculty of Dentistry, Trisakti University, Jakarta, Indonesia. Methods: Saliva sample from children (n = 28, aged 5-10 years old) was collected from healthy children. 2-3 mL of a saliva samples were collected and cultured by using TYS media for total bacterial count. The number of S. mutans in the saliva of these children was counted by real-time PCR methods by using a fluorescence chemical compound green SYBR using 16S rRNA gene specific primers for S. mutans. Results: The average number of total bacterial colony count in saliva was 9.965 ± 2.078 log10 CFU/mL, and the average number of S. mutans in the saliva of children was 8.303 ± 2.351 log10 CFU/mL. Conclusion: The number of S. mutans in the saliva of children in Department of Pediatric, Faculty of Dentistry, Trisakti University was categorized is in the high-risk.